Biomass estimation of Bambusa nutans subspecies cupulata grown at Eastern Terai, Nepal - Oli, B.N.; Kandel, C.M. (Banko Janakari, 2007)
With a view to prepare biomass table of Bambusa nutans subspecies cupulata grown at Belbari, Morang district of Eastern Terai, a total of 150 culms were selected from nintyeight clumps. Measurements of Diameter at 15 cm of the base (D15), vertical height of the culm and green weight of the culm, branches and foliage were taken in the field. The sampled green weight was oven dried in Kathmandu. To estimate the biomass, regression model was developed on the basis of oven dry and green weight. The model used was W = a + b * (D2L). Based on the oven dry weight, the R2 values obtained for culm, branch and foliage components were 90, 82 and 73 per cent respectively. Similarly, R2 values for culm and foliage components on the basis of green weight were 90 and 73 per cent respectively. The R2 values obtained for branch and foliage components were slightly lower as compared to the culm. The validity is to be done before applying this equation to different site conditions. Key words: Biomass, bamboo, Bambusa nutans subspecies cupulata, Nepal Banko Janakari Vol.15(2) 2005 pp34-37